Microemulsion systems: generalities and fields of application - Fernández Rojas, Nathalie (2023)
Microemulsions are two-phase oil-aqueous systems stabilized by a surfactant/cosurfactant system, formed from the spontaneous self-assembly of hydrophobic or hydrophilic parts of surfactant molecules, essential at the industrial level for their unique properties, improving processes and reducing costs. Their main uses in the pharmaceutical, cosmetic, and food industries are to improve the biopharmaceutical and pharmacokinetic properties of drugs, the skin penetration properties, and the stability and solubility of different ingredients. They are obtained by techniques such as phase inversion and phase titration. They are characterized by different techniques that allow obtaining information on the dynamic properties, droplet size, structural arrangement and orientation, molecular aggregation, and system interactions, which allow improving the formulations continuously. Due to their proven advantages and utilities, as well as their potential applications, it is essential to study these systems.